Satellite-driven modeling of the upper ocean mixed layer and air–sea CO2 flux in the Mediterranean Sea - D’Ortenzio, F.; Antoine, David; Marullo, S. (Pergamon, 2008)
The air–sea CO2 flux, the carbon export to the deep layers, and more generally the carbon budgets are presently poorly characterized in the Mediterranean Sea. An approach to the simulation of these fluxes at regional scale is proposed, based on an array of unconnected one-dimensional (1D) physical–biological–chemical coupled models. The rationale is to massively assimilate satellite information, on one hand to derive accurate surface heat fluxes, and, on the other hand, to implicitly account for the horizontal processes not explicitly represented in the 1D scheme. This method is applied here to simulate the upper ocean physical and biogeochemical dynamics of the entire Mediterranean Sea over the years 1998–2004, and at a 0.5° spatial resolution. The mixed-layer annual cycles are validated against the values determined from a database of in situ temperature profiles, demonstrating the validity of the approach in various physical regimes. A validation of the simulated annual cycles of the total inorganic carbon (TCO2) and of the carbon dioxide partial pressure (pCO2) is presented at a measurement site in the northwestern Mediterranean where both properties were determined in 1998–1999 and in 2003–2004. An additional validation of the pCO2 fields is presented using along-track data collected during the “Productivité des Systèmes Océaniques Pélagiques” (PROSOPE) cruise. The basin-scale air–sea carbon budget derived from the model outputs shows that the Mediterranean Sea, over the study period, is close to equilibrium with the atmosphere, with a slight sink for the atmospheric CO2. This is in agreement with the results previously obtained via indirect methods and is supported here by a series of sensitivity studies. A detailed analysis of the pCO2 and TCO2 seasonal distributions in the Mediterranean Sea is provided for the first time. It shows that the biological processes play a major role in shaping the pCO2 seasonal evolution in the eastern and western basins.